Conducting the premature discharge of placenta (Research, Society and Development, 2022)
Introduction: Premature placental detachment is considered obstetric urgency with high potential for maternal and fetal morbidity and mortality. Objective: To analyze the practices of care for pregnant women with premature placental detachment. Methodology: This is an integrative literature review study, the electronic databases Lilacs, BDENF, Scielo and PUBMED were defined as a search source, which are considered as references in scientific production in the health area. Results: Pregnant women with premature placental detachment require a rapid and effective identification of the diagnosis, which helps in the handling and solution of probable adversities. Thus, the work of the multidisciplinary team is essential in the care of pregnant women to achieve better maternal and neonatal results. Conclusion: The approaches for premature placental detachment address as fundamental aspects, among them: clinical and obstetric propaedeutics. Treatment will depend on the degree of detachment (Grade 1, 2 or 3) that is reflected in maternal hemodynamic status and fetal vitality.